Financial implications of modifications to building filtration systems. (February 2015) - Montgomery, James F.; Reynolds, Conor C.O.; Rogak, Steven N.; Green, Sheldon I.
Abstract: Exposure to airborne particles is a serious health concern worldwide and indoor air quality is a critical factor influencing exposure. This work investigates the impact of modified ventilation and filtration system designs to inform building designers, operators, and policy makers of relative effectiveness and costs. Indoor aerosol dynamics, filter cost, and epidemiological models were combined to compare size-resolved indoor particle concentrations, operation costs, and monetized health benefits to occupants within an office building. System airflow and filter efficiency were modified to compare the relative economic implications. Comparisons were made for a number of cities to examine the impact of variation in local air quality, electricity prices, and economic conditions. The operation cost of filtration systems was found to vary by a factor of 3 between cities. The monetized health benefits of filter installations outweigh the operation costs by up to a factor of 10. In the majority of scenarios investigated the net benefits of improved filtration were greatest for the highest efficiency filters. Adding or increasing recirculated and return air in the system provides a net financial benefit due to (indirect) societal health benefits outweighing (direct) operational costs for small increases in airflow but has diminishing returns for large increases. Though system changes are economically beneficial from a societal viewpoint, the costs and benefits are borne by disparate parties and policy changes may be required to ensure optimum design and operation. Highlights: Exposure and cost were modelled to compare financial implications of filter changes. The novel model allows comparison of impacts of policy and design changes. Benefits of improved filtration outweigh added costs by an order of magnitude. Increased filter efficiency and reduced RA flow can reduce cost and improve IAQ.